Protein folding and post-translational modifications (Henry Stewart Talks, 2026)
Protein folding principles, Determinants of protein structure, Chaperones in protein folding, Post-translational modifications, PTMs and protein regulation, Folding, PTMs, and quality control, Disease from folding or PTM errors